2015
DOI: 10.1126/science.aaa5175
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule detyrosination guides chromosomes during mitosis

Abstract: Before chromosomes segregate into daughter cells they align at the mitotic spindle equator, a process known as chromosome congression. CENP-E/Kinesin-7 is a microtubule plus-end-directed kinetochore motor required for congression of pole-proximal chromosomes. Because the plus-ends of many astral microtubules in the spindle point to the cell cortex, it remains unknown how CENP-E guides pole-proximal chromosomes specifically towards the equator. Here we found that congression of pole-proximal chromosomes depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
236
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(251 citation statements)
references
References 40 publications
11
236
1
3
Order By: Relevance
“…By doing this, CENP-E directly supports the alignment of chromosomes to the metaphase plate. [20][21][22][23] In an elegant, laser microsurgery-based study, it was shown that polar ejection forces (PEFs) on chromosome arms (also known as "polar winds") actively contribute to chromosome movement away from the pole. 24 Additional studies revealed that these forces are mainly generated by the microtubule plus-end-directed motor proteins chromokinesins.…”
Section: Introductionmentioning
confidence: 99%
“…By doing this, CENP-E directly supports the alignment of chromosomes to the metaphase plate. [20][21][22][23] In an elegant, laser microsurgery-based study, it was shown that polar ejection forces (PEFs) on chromosome arms (also known as "polar winds") actively contribute to chromosome movement away from the pole. 24 Additional studies revealed that these forces are mainly generated by the microtubule plus-end-directed motor proteins chromokinesins.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of CENP-E by Aurora A regulates the affinity of the motor for microtubules, and is predicted to bias CENP-E to walk along K-fibres towards the spindle equator. Nevertheless, CENP-E-mediated congression does not absolutely require K-fibres (Cai et al, 2009), and a new model of directionality based on the 'tubulin code' has now been proposed (see below) (Barisic et al, 2015). As already discussed, an alternative gradient is the PEF, which generates a force field that is proportional to microtubule density and therefore the proximity to a pole (Cane et al, 2013).…”
Section: Coupling Congression With Position-sensing In the Spindlementioning
confidence: 99%
“…It has been established that a gradient of Plk1 and Ran-GTP concentrations control spindle position (Kiyomitsu and Cheeseman, 2012), and Aurora A forms a spatial gradient that originates at the spindle pole (Ye et al, 2015;Hochegger et al, 2013). Abrogation of the Ran-GTP gradient that is established around aligned chromosomes using a dominant-negative RanT24N mutant has no effect on congression (Barisic et al, 2015). In contrast, the Aurora kinases and Plk1 are known to regulate key microtubule attachment proteins and feedback mechanisms EmsMcClung et al, 2013;Godek et al, 2015;Hochegger et al, 2013;Kettenbach et al, 2011;Kim et al, 2010;Lampson and Cheeseman, 2011;Park et al, 2015), thus providing a potential mechanism for the regulation of kinetochore composition and/or activity during congression.…”
Section: Coupling Congression With Position-sensing In the Spindlementioning
confidence: 99%
See 1 more Smart Citation
“…However, in higher eukaryotes such as fly, frog and humans, CENP-E/kinesin-7 homologues are known to promote chromosome alignment instead of Eg5/kinesin-5 homologues. [37][38][39][40] Since both kinesin-5 and kinesin-7 are plus-end directed processive kinesins, 41 and since yeasts have no CENP-E/kinesin-7 homolog, CENP-E might be a specialized kinesin that evolved to replace the centromeric Eg5/kinesin-5 function in animals. Notably, recent study revealed that the unusually elongated stalk of CENP-E has an essential role in chromosome alignment, because "Bonsai" CENP-E with a shortened stalk is unable to achieve a stable lateral attachment, a prerequisite for chromosome gliding.…”
Section: Evolutionary Conservation Of Mad1-kinesin Pathwaymentioning
confidence: 99%